2020
DOI: 10.1016/j.immuni.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Eomes-Dependent Loss of the Co-activating Receptor CD226 Restrains CD8+ T Cell Anti-tumor Functions and Limits the Efficacy of Cancer Immunotherapy

Abstract: Highlights d TCR signaling and CD8 + T effector program are altered by the absence of CD226 d Dysfunctional CD226 neg CD8 + TILs accumulate in human and mouse tumors d Eomes overexpression is involved in CD226 loss by CD8 + TILs d CD226 loss limits the efficacy of immune checkpoint blockade and CD137 agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 82 publications
4
107
0
Order By: Relevance
“…Taken together the results implicate derepression of DNAM-1 co-stimulatory signaling in response to PD-1 inhibition, similar to the role that has been proposed for CD28 involvement in an anti-PD-1 response (101). Another study has similarly shown that DNAM-1 is required for PD-1 blockade anti-tumor activity in pre-clinical mouse models (102). In accordance with these results, DNAM expression on TILs was shown to correlate positively with the response to PD-1 blockade in melanoma patients (103).…”
Section: Pd-1: a Player In The Dnam-1 Axis?supporting
confidence: 81%
“…Taken together the results implicate derepression of DNAM-1 co-stimulatory signaling in response to PD-1 inhibition, similar to the role that has been proposed for CD28 involvement in an anti-PD-1 response (101). Another study has similarly shown that DNAM-1 is required for PD-1 blockade anti-tumor activity in pre-clinical mouse models (102). In accordance with these results, DNAM expression on TILs was shown to correlate positively with the response to PD-1 blockade in melanoma patients (103).…”
Section: Pd-1: a Player In The Dnam-1 Axis?supporting
confidence: 81%
“…CNV analysis showed that genes related to chemokines, cytokines, and immune response receptors, including CD226, CXCL9, CXCL11, and IL2, were deleted to varying degrees in the C3 subtype. Moreover, the low expression of these genes was significantly related to poor prognosis in patients with OC, and we found that they had previously been validated as associated with tumor immune response and immunotherapeutic efficacy (47)(48)(49).…”
Section: Discussionmentioning
confidence: 64%
“…Most recent studies on CD226 downregulation by EOMES and CBL-B and its impact on antitumor activity of CD8 + T cells also highlight the crucial role of CD226 for effective cancer immunotherapy (26,74).…”
Section: Cd226mentioning
confidence: 99%
“…A recent study using preclinical mouse models reported that inhibiting CD112R promotes an antitumor immune response by restoring T-cell activities. Pmel-1 CD8 + T cells isolated from Pmel-1 TCR-CD112Rdeficient mice show augmented effector responses, including CD107 expression and effector cytokine production upon gp100 [25][26][27][28][29][30][31][32][33] stimulation and subsequent co-culture with B16/F10 tumor cells expressing mhgp100 and Nectin-2 (85). Consistent with the in vitro results, MC38 tumor growth was decreased in http://bmbreports.org Fig.…”
Section: Cd112rmentioning
confidence: 99%